Training pathways in the integrated context for disabled students and other atypical conditions - Redig, Annie Gomes (2019)
The present work, based on a review of the specific literature of the area, proposes to discuss the formative itinerary and strategies that can be used to assist in the transition process from school to the independent life of students with disabilities. When we debate the policy of Inclusive Education, one of the challenges is the schooling of young people and adults with disabilities in Primary and Secondary Education. Therefore, the school needs to construct inclusive methodologies that provide this disabled student with possibilities for social and labor insertion, together with adequate schooling that includes aspects related to the construction of knowledge, psychosocial and occupational development. In this direction, we believe that with the elaboration of individualized pedagogical practices linked and organized by documents such as the Individualized Education Plan (IEP) and Individualized Transition Plan (ITP), this training course can be constructed in a way that allows the school transition for independent living to happen in a structured and efficient way.